Health care monitoring system an application of IOT using WI-FI - Grewal Dangi, Kusum; Yadav, Mohit; Malhotra, Shubham (International Journal of Engineering and Technology, 2018)
With emerging networking technologies and micro electromechanical devices the world is full of opportunities to get connected and stay connected seamlessly. To facilitate this connectivity among every possible object in the world, Internet of things (IoT) has emerged. In this project we have made a hardware consists of a Micro-Controller, Pulse Measurement Sensor, and Body Temperature Sensor, Wi-Fi module, LCD and some interfacing module. So basically this hardware will take reading from the sensors and after processing that it will show the readings/measurement on LCD as well as on a server which is online. The major thing in this project is that one can monitor the patient at anywhere in the world with the use of internet, the doctor keep the track of your health and measurement of heart rate, blood pressure, etc. In this way you always be in touch with the Doctor, no matter where you are. Then if something happen apparently the message goes to the doctor before it becomes the emergency situation and also if a patient is hospitalized then patients would also be allowed to leave hospitals and clinics earlier, as professionals are enabled to monitor them from home.Â